Truman - McCullough, David (New York Simon & Schuster Paperbacks, 1992)
Pulitzer Prize winner and #1 New York Times best-selling author of John Adams (RB# 96791), David McCullough pens a fascinating and sweeping biography of America's 33rd president. Born and raised on the Missouri frontier, Harry S. Truman began life as a clerk, farmer, and soldier, but grew to be one of history's most courageous leaders.
Include Illustration, Notes and Index
Keywords: United States -- Presidents